中國傳統身體觀與當代墮胎難題: The Issue of Body and the Contemporary Dilemma of Abortion: A Critical Remark from a Traditional Chinese Perspective - WANG, Jue (International Journal of Chinese & Comparative Philosophy of Medicine, 2007)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 本文揭示了在當代西方墮胎爭論背後起作用的身體圖式，以及這種身體圖式如何使墮胎問題最終在西方語境中成為沒有答案的難題。並援引醫家和儒家的思想材料，說明中國傳統身體觀如何更平衡地解決了同一個身體中的母親與胎兒的關係問題，從而既避免了西方語境中的陷阱，又因為更貼近懷孕身體的真實關係而在應用上具有倫理優勢。 Abortion is a subject of much controversy in contemporary Western culture. However, the heated debate produces a dilemma: pro-life or pro-choice. For the pro-life advocates, the fetus is regarded as a person and therefore has the absolute right to life, which is undeniable in any case. Even when pregnancy threatens the mother's life, the mother has no right to take the innocent life of the fetus; In other words, the choice of life or death should submit to pure chances, as some critics uphold. On the other hand, however, the pro-choice advocates claim that the pro-life argument is incoherent and radical, since the right to life should not include the right to use another person's body. In their view, the woman should enjoy complete control on her body as on her house. The woman has the right to abort, as long as she has the right to decide what happens in her body: no doubt the fetus has the right to life, but unfortunately, not in this body. The ostensibly incompatible positions of the “ pro-life" and the "pro-choice” actually share the same all-or-nothing strategy which is predetermined by the same image of the body. In the Western tradition, the body is viewed as a thing, and being a person is equated with controlling a body. Accordingly, it is inclined to obscure the existence of the mother which is viewed as only chora. There is less debate on abortion in the context of Chinese culture. This does not mean that Chinese people are more barbaric over such issues, as some Western scholars imagine. This paper aims to propose that Chinese traditional thought has a different system of language about the issue of abortion based on its own body-schema. It argues that this language system may avoid the dilemma mentioned above. Contrary to the Western body-schema, the Chinese body-schema does not admit the dualism of body and soul, and hence does not emphasize the absolute control of the person (or the soul) on the body. The body in the Chinese traditional thought is not viewed as a closed organism kept in dualism, but a continuum of one and the same level, or a texture, which keeps returning to itself by intertwining everything born from it, especially in terms of qi〔氣〕- vital energy - therefore there is no fixed limit between body and soul, or between my body and another person's body. Concerning the issue of abortion, the Chinese body-schema can be further examined in three contexts. First, in the context of procreation, the sexual bodies are neither viewed as homogeneous nor heterogeneous, but coexist as symbiosis (of yin and yang〔陰陽〕): that is, the unity of two organismic processes which require each other as a necessary condition for being what they are. This makes it possible for Chinese traditional thought to evaluate the meaning of the mother clearly, which is, however, depressed in the Western tradition. Second, in the context of the development of the fetus in the womb, the fetus is viewed as an essential part of the mother, like plants having flowers and fruits, or trees having roots. Relations of parents to children or children to parents are like two parts of a single body or the same breath / vital energy separately breathed, which can find direct responses from each other. Such a mutual influence becomes more and more apparent, which serves as an important limitation on abortion after the pregnancy lasts beyond three months. Finally, in the context of Confucianism, everyone's body is viewed as derived and inseparable from his parents, which suggests a new ethical horizon: the choice of moral values and behaviors is up to qin intimacy, 〔親〕. Qin is neither individuals nor other bigger units (e.g. family, nation); it can never be substantiated, but is always already there as a vortex: everything having originated from it keeps returning to it, and just in this tension everything gets its proper ethical position. For example, in the case of abortion, not the rights, but the concrete ethical relations of the family, should first be taken into consideration. Under some circumstances, abortion may be a more responsible decision for other family members or qin , yet the fetus is still of irreducible importance, for qin naturally covers the fetus. In conclusion, the Western one-sided body-schema (in which one body is shared by two persons) is far from showing the real relation in pregnancy. It leads to an all-or-neither strategy and thus falls into dilemma. In contrast, the Chinese body-schema can hit the balance between the woman and the fetus, or between the pregnant body and the socially ethical body (qin). The Chinese body-schema is closer to the concrete situation of the pregnant woman and thus has ethical advantages to overcome the dilemma in practice. DOWNLOAD HISTORY | This article has been downloaded 168 times in Digital Commons before migrating into this platform.